VICTIM-OFFENDER MEDIATION IN INDIA’S CRIMINAL ADMINISTRATION: AN ANALYSIS OF EMERGING PRACTICES THROUGH RESTORATIVE PRINCIPLES (International Journal of Food and Nutritional Sciences, 2022)
India has a long history of the resolution of disputes outside the formal judicial system. Thiswas in use since it provided an opportunity to the victim to resolve the dispute in a matter,they deem fit and suitable. In the field of criminal law, such a mechanism has the elements ofrestorative justice which promotes out of Court settlement.